The presence of foreign capital and the internationalization of Portuguese industrial SMEs - Luís Pacheco; Carla Azevedo Lobo; Isabel Maldonado (Journal of Risk and Financial Management, 2022)
The objective of this paper is to empirically examine the relationship between the firms' ownership and control structure, in particular the presence of foreign capital, and their internationalization levels, measured in terms of intensity and diversification. The international performance of Portuguese SMEs, which is crucial for the domestic economy's growth, depends on a multitude of factors, with the existence of foreign investment inflows directed to industrial SMEs being a usually forgotten factor. This paper fills that gap using a balanced panel data of 5722 firms for the period from 2010 to 2017, researching if the presence of foreign capital influences the level and scope of internationalization, and controlling the effects of other variables such as profitability, age, size, indebtedness and sector of activity. The origin of foreign capital is also considered, being researched if issues of institutional or development differences exert any influence over firms' internationalization. The results evidence that the presence of foreign shareholders in SMEs positively influences internationalization and that the distance variable positively correlates with the internationalization measures. Moreover, there seems to exist a non-linear relationship between the development level of the country of origin of the share capital and internationalization, with the results indicating that firms with share capital originating from more advanced countries attain a higher degree of internationalization. As SMEs in Portugal face increasing competition, joining hands with resource-rich investors such as foreign corporations and institutional investors would be a fruitful strategy to enhance the international competitiveness of Portuguese firms.
Keywords: G32; F23; 330; ownership structure; internationalization; foreign investment; SMEs; manufacturing sector